Wheatgrass microgreen with high antioxidants content in an urban indoor farming system - Myrea Chalil; Karlia Meitha; Ramadhani Eka Putra; Fathia Aulia Rahmah; Ridho R Sinatra; Anindha Ajeng Putri Winanta (School of Life Sciences and Technology, Institut Teknologi Bandung, 2022)
Urban lifestyle is identical to stressful life and sedentary habit, leading to the increase of chronic conditions such as diabetes and cardiovascular-related diseases. Antioxidants are renowned for maintaining cellular function by quenching radicals produced in stressful conditions or infection. Fresh fruits and vegetables are the primary sources of antioxidants, but the long postharvest and transport system may reduce the benefits for the urban population. Hence, we designed a cultivation method to produce wheatgrass microgreens with high antioxidants in an urban indoor farming system. Generally, plants require light at the wavelength of 663 and 642 nm (red) and 430 nm and 453 nm (blue) to allow photosynthesis and production of secondary metabolites, such as antioxidants. We applied the LED lights with an RGB ratio of 91R/9B, 83R/17B, 47R/53B, 35R/65B, and white florescent as the control. Our results showed that 91R/9B reduced fresh mass and chlorophyll content, which might be due to the suppression of photosynthesis capacity. Interestingly, we found a significant (p<0.05) increase in carotenoids and flavonoid contents due to light combinations of 35R/65B and 83R/17B, respectively. However, the total antioxidants capacity was similar among all treatments. Carotenoids and flavonoids are among the antioxidants with a significant role in decreasing the risks of chronic diseases and their potential as antiviral agents. This cultivation system of wheat microgreen could be a promising solution to routinely supply carotenoids and flavonoids to the urban population. Further, it is also considered more environmentally friendly as it could be performed in a limited amount of land (vertically) and potentially use less energy for distribution.